1992
DOI: 10.1111/j.1365-2958.1992.tb01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of FliY, a novel component of the Bacillus subtilis flagellar switch complex

Abstract: The Bacillus subtilis gene encoding FliY has been cloned and sequenced. The gene encodes a 379-amino-acid protein with a predicted molecular mass of 41,054 daltons. FliY is partly homologous to the Escherichia coli and Salmonella typhimurium switch proteins FliM and FliN. The N-terminus of FliY has 33% identity with the first 122 amino acids of FliM, whereas the C-terminus of FliY has 52% identity with the last 30 amino acids of FliN. The middle 60% of FliY is not significantly homologous to either of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
2
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 29 publications
1
55
2
1
Order By: Relevance
“…P24073 ; 40 % identity in 173 overlapping amino acids, 46 % of FliY). The protein encoded by fliY (FliY) in B. subtilis is an essential component of the flagellar motor-switch complex (C-ring) and represents the Gram-positive counterpart of the Gram-negative FliN (Bischoff & Ordal, 1992). iments with the chromosomal DNA derived from strains NCIB 8122 and MP01.…”
Section: Strain Mp01 Is a Fliy Null Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…P24073 ; 40 % identity in 173 overlapping amino acids, 46 % of FliY). The protein encoded by fliY (FliY) in B. subtilis is an essential component of the flagellar motor-switch complex (C-ring) and represents the Gram-positive counterpart of the Gram-negative FliN (Bischoff & Ordal, 1992). iments with the chromosomal DNA derived from strains NCIB 8122 and MP01.…”
Section: Strain Mp01 Is a Fliy Null Mutantmentioning
confidence: 99%
“…Spreading of B. cereus, briefly discussed in a general review on bacterial surface translocation (Henrichsen, 1972), has been reported to be due to swimming motility only, brought about by individual cells that do not exhibit hyperflagellation or elongation. In this report, we demonstrate that B. cereus is capable of swarming differentiation and that the production of differentiated swarm cells requires the activity of fliY (Celandroni et al, 2000), the homologue of which in Bacillus subtilis encodes an essential component of the flagellar-switch complex (C-ring) controlling the direction of flagellum rotation (Bischoff & Ordal, 1992). Complementation of a fliY deletion, identified in a motile but non-swarming and non-chemotactic spontaneous mutant of B. cereus, restores the ability to produce differentiated swarm cells as well as to respond to chemoattractants.…”
Section: Introductionmentioning
confidence: 99%
“…Its genome revealed a FliY-like protein (coordinates 706,930 -707,957) (25), which through an (authentic) frameshift appears to be cut into two proteins, a FliY N-terminal part and a FliN. It appears likely that the FliN part is actually expressed as both S. typhimurium fliN and B. subtilis fliY mutants are not flagellated (11,12), yet T. maritima MSB8 is motile (26) and its genome does not seem to encode for an alternative FliN. This might be an example of how FliN originated from FliY by loss of its N-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…1A) (7). The fact that a Salmonella typhimurium fliN mutant could be partially complemented by B. subtilis fliY indicates that these two proteins share a common function as a component of the flagellar switch (11).…”
mentioning
confidence: 95%
See 1 more Smart Citation